2018
DOI: 10.1038/s41598-018-20130-9
|View full text |Cite
|
Sign up to set email alerts
|

Global ubiquitination analysis reveals extensive modification and proteasomal degradation of cowpox virus proteins, but preservation of viral cores

Abstract: The emergence of Variola virus-like viruses by natural evolution of zoonotic Orthopoxviruses, like Cowpox virus (CPXV), is a global health threat. The proteasome is essential for poxvirus replication, making the viral components interacting with the ubiquitin-proteasome system attractive antiviral targets. We show that proteasome inhibition impairs CPXV replication by prevention of uncoating, suggesting that uncoating is mediated by proteasomal degradation of viral core proteins. Although Orthopoxvirus particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 64 publications
1
10
0
1
Order By: Relevance
“…Indeed, we found that MG132 rescues 69% of host proteins from degradation including HDAC5, suggesting that many of the downregulated proteins may be specifically targeted to the proteasome. This finding is consistent with a recent analysis of protein ubiquitylation during cowpox virus infection ( Grossegesse et al., 2018 ). Transcriptional mechanisms may nevertheless play an important role in protein downregulation.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, we found that MG132 rescues 69% of host proteins from degradation including HDAC5, suggesting that many of the downregulated proteins may be specifically targeted to the proteasome. This finding is consistent with a recent analysis of protein ubiquitylation during cowpox virus infection ( Grossegesse et al., 2018 ). Transcriptional mechanisms may nevertheless play an important role in protein downregulation.…”
Section: Discussionsupporting
confidence: 93%
“…Modification of ubiquitination can be important for antiviral defense and virus replication, and viral proteins can also be modified. 17 , 22 , 23 The extent of ubiquitination of SARS-CoV-2 proteins is unclear. Therefore, we analyzed SARS-CoV-2 proteins for the presence of ubiquitinated residues.…”
Section: Resultsmentioning
confidence: 99%
“…To date, many viral proteins have been reported to be ubiquitinated, including influenza A virus-encoded NP, M2 and PB1 [25][26][27][28], Dengue Virus-encoded NP [29], and 54 viral proteins encoded by the wellcharacterised cowpox virus strain [30]. In ubiquitinated proteins, Ub is frequently found to be covalently conjugated to Lys residues, but non-Lys residues of substrates such as serine (Ser), threonine (Thr) and cysteine (Cys) are also modified in rare cases.…”
Section: Identification Of Viral Proteins Modified By Ubiquitinationmentioning
confidence: 99%